STUDENTS’ ATTITUDE TOWARD PEER-ASSESSMENT: THE CASE OF ADAMA SCIENCE AND TECHNOLOGY UNIVERSITY FOURTH YEAR COMPUTER SCIENCE AND ENGINEERING STUDENTS, ETHIOPIA - LIKISA , KUMSA DONIS (IJRDO- Journal of Educational Research, 2019)
The main objective of this study was to examine students’ attitude toward peer-assessment (PA) and their understanding of the benefits of PA. To achieve its objective, the study employed the System Theory. The main sources of information were 160 fourth year undergraduate students. All students taking cognitive psychology were included in the study. Questionnaire, focus group discussion and interview were used to gather information from the respondents. In the analysis of data, mean, SD, correlation and t-test were employed. The study reveals that students’ attitude toward PA varies with their understanding of the benefits and the degree to which they involved in PA. With careful preparation, design and execution, students have a positive view of PA and understand its educational benefits. Finally, recommendations were given based on the major findings to improve the quality of students’ PA.